AKTIVITAS TAMPING KEBERSIHAN SEBAGAI BENTUK KOMUNIKASI ASERTIF DALAM PEMBINAAN WARGA DI RUTAN DEPOK KELAS I - Dipo Krishyudi Ono; Roni Jayawinangun; Prameswari Handayani (UNIVERSITAS PAKUAN, 2022)
One of the important roles to keep the inmates from being aggressive and preventing behavior that causes riots requires an accurate communication pattern strategy approach, namely assertive communication. Assertive communication communicates what you think, feel, and want clearly and unequivocally to others without feeling intimidating, violating, and belittling the rights of yourself and others. Depok Class 1 Rutan has a cell block with a total of 400 inmates out of a total of 1100 inmates who are guarded by one officer by taking turns divided into three shifts in 1 day. Inmates who are employed at the detention center or called tamping, Impact experienced from experience their time serving as companion prisoners is an increase in personal, social and vocational. The study concluded that being a companion prisoner has an impact on change. Positive self-esteem and giving them the opportunity to become more skilled and productive people after They were released from prison one of them Named Joko is a resident of a special cell block for cleaning, he helps officers clean the detention center and maintains order and ensures that the condition of the detention center is clean and well-maintained every day. This research uses the rapid-ethnography Research method with participant observation and in depth interviews to find information on how the relationship between employees and tamping is related to uncover the motivations of the inmate's companion prisoners and the impact of the role he changed himself during his stay in prison. in creating compliance, law compliance. to maintain security and order in the class 1 detention center Depok